Symptoms as the Main Predictors of Caregivers' Perception of the Suffering of Patients With Primary Malignant Brain Tumors. Issue 2 (March 2016) - Zeleníková, Renáta; Ren, Dianxu; Schulz, Richard; Given, Barbara; Sherwood, Paula R.
Abstract : Background: The perception of suffering causes distress. Little is known about what predicts the perception of suffering in caregivers. Objective: The aims of this study were to determine the predictors of caregivers' perceptions of the suffering of patients with a primary malignant brain tumor and to find to what extent perceived suffering predicts the caregivers' burden and depression. Methods: Data were obtained as part of a descriptive longitudinal study of adult family caregivers of persons with a primary malignant brain tumor. Recruitment took place in outpatient neuro-oncology and neurosurgery clinics. Caregiver perception of care recipient suffering was measured by 1 item on a scale from 1 to 6. Results: The sample of caregiver interviews 4 months after recipients were diagnosed consisted of 86 dyads. While controlling for age, years of education, tumor type, being a spousal caregiver, spiritual well-being, and anxiety, perception of overall suffering was predicted by such symptoms as difficulty understanding, difficulty remembering, difficulty concentrating, feeling of distress, weakness, and pain. Caregivers' perception of the patient's degree of suffering was the main predictor of caregiver burden due to schedule 4 months following diagnosis. Conclusions: Care recipient symptoms play an important role in caregivers' perception of the care recipients' suffering. Perception of care recipient suffering may influence caregiver burden. Implications for Practice: Identifying specific predictors of overall suffering provides meaningful information for healthcare providers in the field of neuro-oncology and neurosurgery.